2014
DOI: 10.1016/j.ijsu.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tissue damages caused by endoscopic lumbar discectomy and traditional lumbar discectomy: A randomised controlled trial

Abstract: The PELD had less damage to human tissues than the traditional OD. PELD has a clear promotional value in clinical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 22 publications
2
56
0
4
Order By: Relevance
“…Endoscopic procedures for treatment of spinal diseases firstly came out in 1992 and have been widely applied in clinical practice for lumbar spine diseases, as the rapid development of endoscopic technology. Recent studies have reported that they could achieve equal curative effect with less trauma and shorter hospital stay compared to traditional surgeries [3][4][5][6]. Our results showed that 71 (82.6%) out of 86 cases achieved good or excellent surgical outcomes which further confirmed that PELD was an effective and reliable method for the treatment of LDH.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Endoscopic procedures for treatment of spinal diseases firstly came out in 1992 and have been widely applied in clinical practice for lumbar spine diseases, as the rapid development of endoscopic technology. Recent studies have reported that they could achieve equal curative effect with less trauma and shorter hospital stay compared to traditional surgeries [3][4][5][6]. Our results showed that 71 (82.6%) out of 86 cases achieved good or excellent surgical outcomes which further confirmed that PELD was an effective and reliable method for the treatment of LDH.…”
supporting
confidence: 78%
“…Patients with lumbar disc herniation (LDH) usually present with symptoms like pain, numbness, and weakness, which have a negative influence on their social functions [1,2]. Percutaneous endoscopic lumbar discectomy (PELD) first appeared in 1992 [3] and has been widely used in clinical practice for lumbar spine diseases due to less invasiveness and faster recovery compared with traditional surgery [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…And Lowell et al 19 reported that three patients undergoing open discectomy got infected after administration of perioperative steroids. Infections are rarely seen owing to the measures of continuous irrigation, prophylactic antibiotics, minimal tissue damage 20 and short surgery time. Other adverse effect such as osteoporosis is rare.…”
Section: Discussionmentioning
confidence: 99%
“…При этом результаты сравнительного анализа марке-ров воспаления и маркеров болевого синдрома, получен-ные L. Pan и соавт. [21], подтверждают значительные пре-имущества перкутанного эндоскопического метода по сравнению с микрохирургическим методом. C. Schizas [22] среди недостатков эндоскопических методов отмечает низкое качество изображения, которое, в сравнении с микроскопическим, не передает объема и глубины.…”
Section: эффективность метода эндоскопической дискэктомииunclassified